Applying Interview-Research Methods Using Generative AI Technology: An Action Research Study with Graduate Students in Mock Research Teams - Brown, Barbara; Sabbaghan, Soroush (The Canadian Journal of Action Research, 2025)
In this study, we aimed to examine graduate students’ experience when working with peers to complete a learning task focused on conducting a program evaluation in a qualitative research course. A generative artificial intelligence (GenAI)-powered platform was incorporated to support an experiential learning activity designed by the instructor-researcher. A collaborative action research approach was employed through the planning, enactment, and reflective phases of the study wherein four graduate students who engaged with the platform were interviewed to help improve the next iteration of the learning activity in future courses. This study contributes to the pedagogical discourse about the use of experiential learning for teaching and learning qualitative research methods.